GEOGRAM: Learning through play - Mohd Mansor, Nur Syahirah; Abd Ghofur, Nur Aliah Syahirah; Syed Ahmad Za'im, Sharifah Syazwani; Kechil, Rafizah; Mohd Mydin, Azlina (2022)
The mathematical study of shapes and space is known as geometry. In order to solve problems involvinggeometry, students should be able to know the formulas for the basic shapes and spaces. Problems with calculations will arise due to a lack of knowledge and awareness of skills in calculating and identifying basic geometry's formula. The purpose of this GeoGram is to provide an edutainment experience for students to review and improve their knowledge of basic geometry formulas. We want to make a game that will teach students simple and rapid self-learning tactics that they may use at any time. We used a PowerPoint spinning-wheel created by tekhnologic and a tangram created by mathigon as a game platform. We modified the spinning wheel by including a task for the player to perform. The geometry's formula is also visible near the spinning wheel. After spinning the wheel, the player must accomplish the objective of creating a diagram using the tangram platform by applying the formula provided. The use of GeoGram, which has an edutainment component, will aid students in improving their familiarity of geometry's formulas. GeoGram can be utilised in STEM programmes involving secondary school and higher education students. This is because they can see how mathematics is used in their lives and surroundings, and students' knowledge and enthusiasm in mathematic subjects will grow. This is due to the GeoGram's development considering learning theories, as well as an awareness of students' requirements and interests.